2020
DOI: 10.3390/v12030313
|View full text |Cite
|
Sign up to set email alerts
|

Eradicating the Scourge of Peste Des Petits Ruminants from the World

Abstract: Peste des Petits Ruminants (PPR) is a highly contagious viral disease of both domestic (goats and sheep) and wild ruminants. Caused by a morbillivirus, that belongs to the family Paramyxoviridae. The disease is clinically and pathologically similar to rinderpest of cattle and human measles. PPR is one of the most economically devastating viral diseases of small ruminants. In April 2015, the Food and Agriculture Organization of the United Nations (FAO) and the World Organisation for Animal Health (OIE) launched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Thus, control measures for ongoing livestock disease outbreaks in the region (e.g. foot and mouth disease, Rift Valley fever), the peste des petits ruminants eradication campaign, and for endemic diseases of importance like contagious caprine pleuropneumonia are critical (Njeumi et al 2020 ; ProMED-mail 2020a , b ). Decreased or limited access to pastoral areas by animal health personnel can harm these efforts.…”
Section: Pastoral Food and Livelihood Security: Offsetting The Secondmentioning
confidence: 99%
“…Thus, control measures for ongoing livestock disease outbreaks in the region (e.g. foot and mouth disease, Rift Valley fever), the peste des petits ruminants eradication campaign, and for endemic diseases of importance like contagious caprine pleuropneumonia are critical (Njeumi et al 2020 ; ProMED-mail 2020a , b ). Decreased or limited access to pastoral areas by animal health personnel can harm these efforts.…”
Section: Pastoral Food and Livelihood Security: Offsetting The Secondmentioning
confidence: 99%
“…Munir (72) reported that most epidemics in wild small ruminants appear to originate from nearby infected domestic sheep and goats and although there is no plausible evidence of self-sustaining PPRV infection in wild ruminant populations, the potential importance of wildlife in the epidemiology of the disease cannot be ignored. The endemicity of PPR therefore poses a threat, not only to the pastoralists and their livelihoods, but potentially also to the conservation of wildlife and endangered wild small ruminant species (24,52,73).…”
Section: Discussionmentioning
confidence: 99%
“…Peste des petits ruminants (PPR), is a highly contagious, devastating viral disease of domestic and wild ruminants, primarily affecting goats and sheep [490,491]. Peste des petits ruminants virus (PPRV) is a negative sense single stranded-RNA morbillivirus, of the family Paramyxoviridae, that is closely related to other members of the genus such as rinderpest, measles, and canine distemper [492].…”
Section: Peste Des Petits Ruminantsmentioning
confidence: 99%